An Overview Regarding Christian Communities in Cochinchina (From the 16th to the 18th Century) - Trieu Huy Ha (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This article aims to introduce an overview of the development of Christian Congregations and their contribution to local culture and rituals in Cochinchina. Historical methods and source materials exploitation have been employed to prove that Christianity overcame the arduous ordeal of a messy historical background of local history and the deep-rooted culture of local belief to position itself in Cochinchina. The establishment of new communities of Christians contributed to gathering refugees to reclaim the southern territory and helped accelerate Vietnamese-Western acculturation by spreading positive values of the new culture among Christian communities. Received 25 th August 2021; Revised 16 th February 2022; Accepted 16 th March 2022